NATIONAL ECONOMIC GROWTH AND REGIONAL DEVELOPMENT IN CHILE - Brúderová, Ivana (2015)
Topic of territorial inequalities has gained importance recently, with increased number of authors investigating the topic in Latin American region, where it became a serious issue. Chilean incapability to export a benefits of its national growth to the regions, are a matter of concern of Chilean government as territorial inequalities already prevents the country in further increasing its level of national aggregate growth. Through analysis of economic, demographic, and labor market indicators over the 2000-2012 period on regional level I identify slow and fast growing regions, regions endangered by population decline and answer a question if national Chilean economic growth is visible also in its regions or strictly concentrated in a capital, Santiago. The differences in results of calculations based on administrative and functional regions division demonstrate the need of change in regional approach of Chilean National statistical office such as putting greater focus on rural-urban partnerships in order to unlock the growth potential of Chilean regions.